2015
DOI: 10.1590/1807-3107bor-2015.vol29.0033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotic fermented milk on biofilms, oral microbiota, and enamel

Abstract: The aim of this study was to evaluate in vitro and in vivo the effects of 2 brands of probiotic fermented milk on biofilms, oral microbiota, and enamel. For the in situ experiment, ten volunteers wore palatine devices containing four blocks of bovine dental enamel over 3 phases, during which 20% sucrose solution, Yakult ® (Treatment A), and Batavito ® (Treatment B) were dropped on the enamel blocks. Salivary microbial counts were obtained and biofilm samples were analyzed after each phase. For the in vivo expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 30 publications
0
15
0
7
Order By: Relevance
“…Regarding whether Yakult ® reduced salivary levels of S. mutans , clinical studies showed controversial results 22, 23, 24, 25. The present study showed that Yakult ® could inhibit the growth of S. mutans .…”
Section: Discussionmentioning
confidence: 45%
See 4 more Smart Citations
“…Regarding whether Yakult ® reduced salivary levels of S. mutans , clinical studies showed controversial results 22, 23, 24, 25. The present study showed that Yakult ® could inhibit the growth of S. mutans .…”
Section: Discussionmentioning
confidence: 45%
“…This finding echoed with a clinical study showing that daily mouth-rinsing with Yakult ® for 7 constitutive days reduced salivary levels of S. mutans 22 . While three other studies did not show reduction of salivary levels of S. mutans after Yakult ® consumption,23, 24, 25 the reason for the inconsistent observation is still unclear. A potential explanation is that the study designs of these clinical studies varied and might not be standardized among studies, as suggested by systemic reviews 3 , 4 .…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations